The New Faces of Political Islam in the Middle East A Survey of 15 Countries after the Arab Spring - Wahyudhi, Nostalgiawan; Basyar, M. Hamdan; Mashad, Dhurorudin; Ghafur, M. Fakhry; Margiansyah, Defbry (Springer Nature Singapore : Imprint: Springer, 2025)
XVII, 182 p. 14 illus., 12 illus. in color.